Herpes simplex virus-induced upregulation of inflammatory cytokines in human gingival fibroblasts - Yu Zhang; Kalam Lo; Chunmei Wang; Guoliang Zhou; Xiping Feng; Jing Ni; Xi Chen (Virology Journal)
Abstract Herpes simplex virus type 1 (HSV-1) is the leading pathogen in the maxillo-facial region, affecting millions of individuals worldwide. Its periodic reactivation aligns with the most common course pattern of periodontal disease. The present study used RNA sequencing to investigate the transcriptomes of human gingival fibroblasts (HGFs) following HSV-1 infection from the early to late stages (12–72 h). At the early stage of infection (12 h post-infection), the most upregulated genes were interferon (IFN) regulatory factor family members, toll-like receptor (TLR) family members, IFN-β1, interleukin (IL)-1, C-C motif ligands, chemokine (C-X-C motif) ligands (CXCLs), and tumor necrosis factor (TNF). The strongest differential expression was observed in TNF, nucleotide-binding oligomerization domain-like receptor (NLR), and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling pathways. At the late stage of infection, the most upregulated genes were CXCLs and ILs. The differentially expressed genes were divided into nine clusters, according to the time series expression trend. Next, the prominent activation of TLRs, retinoic acid-inducible gene I-like receptor signaling, NLRs, and downstream IFNAR-JAK-STAT signaling pathways were observed via a modified HSV-1 infection map. The HSV-1-induced upregulation of inflammatory cytokines in HGFs may drive inflammatory processes in periodontitis. The dynamic variations in mRNAs in HGFs from the early to late stages after HSV-1 infection can provide an analytical framework for determining the host anti-viral defense response to antagonize HSV-1 infection in periodontal tissues.